Male greater sage‐grouse movements among leks. Issue 3 (2nd January 2017) - Fremgen, Aleshia L.; Rota, Christopher T.; Hansen, Christopher P.; Rumble, Mark A.; Gamo, R. Scott; Millspaugh, Joshua J.
ABSTRACT: Movements among leks by breeding birds (i.e., interlek movements) could affect the population's genetic flow, complicate use of lek counts as a population index, and indicate a change in breeding behavior following a disturbance. We used a Bayesian multi‐state mark‐recapture model to assess the daily probability of male greater sage‐grouse ( Centrocercus urophasianus ) interlek movements and estimate factors influencing movements among leks. We fitted 145 males with solar Argos global positioning systems platform transmitter terminals over 4 years (2011–2014) in Carbon County, Wyoming, USA. The daily probability of a male sage‐grouse moving among leks ranged 0.003 (95% CI = 0.000–0.010) in 2011 to 0.010 (95% CI = 0.001–0.021) in 2013, indicating high daily lek fidelity throughout the season, although there was a 5–42% chance annually a male would move at least once to another lek throughout the season ( x ¯ days analyzed/M = 55 ± 3.3 days [SE]). Interlek movement probabilities were strongly affected by day of year, peaking early in the lek season. Interlek movements were positively associated with elevation. Seasonal interlek movements occurred more frequently than previously reported, and can bias lek counts in early spring as males move from low to high elevation leks, which reinforces interlek movements as a critical component of lek ecology. © 2016 The Wildlife Society. Abstract : We evaluated male greater sage‐grouse movements among leks using multi‐state mark‐recapture models, and found male sage‐grouse were more likely to move among leks early in the breeding season, and to leks at higher elevations. Our results suggest avoiding lek counts early in spring to minimize double‐counting or failing to count males that move from low to high elevation leks early in the breeding season.